2018
DOI: 10.24972/ijts.2018.37.2.119
|View full text |Cite
|
Sign up to set email alerts
|

A Neurotheological Approach to Spiritual Awakening

Abstract: A neurotheological approach suggests an analysis of spiritual awakening experiences by combining phenomenological data with neuroscience. This paper presents a synthesis combining information on the thoughts, feelings, and experiences associated with spiritual awakening experiences and neurophysiological data, primarily from neuroimaging studies, to help assess which brain structures might be associated with these experiences. Brain structures involved with emotions correlate with emotional responses while are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The majority of research has been on temporary forms of the experience. Very little empirical study of self-transcendent states that are persistent has been conducted (e.g., Butlein, 2005; Costeines, 2009; Kilrea, 2013; Martin, 2020; McCormick, 2010; Taylor, 2013), including a small number of neuroscience investigations (e.g., Davis & Vago, 2013; Josipovic, 2014; Newberg & Waldman, 2018).…”
Section: Attempts At Measuring Self-transcendencementioning
confidence: 99%
See 2 more Smart Citations
“…The majority of research has been on temporary forms of the experience. Very little empirical study of self-transcendent states that are persistent has been conducted (e.g., Butlein, 2005; Costeines, 2009; Kilrea, 2013; Martin, 2020; McCormick, 2010; Taylor, 2013), including a small number of neuroscience investigations (e.g., Davis & Vago, 2013; Josipovic, 2014; Newberg & Waldman, 2018).…”
Section: Attempts At Measuring Self-transcendencementioning
confidence: 99%
“…Transient and persistent forms of self-transcendence occur in individuals across ages, ethnicities, and backgrounds (Martin, 2020). They are reported in spiritual and religious individuals, as well as atheists and agnostics alike (Newberg & Waldman, 2006, 2018; Newberg et al, 2001).…”
Section: Attempts At Measuring Self-transcendencementioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been some progress in recent research exploring the experience of nonordinary states and mental health, the evidence suggests a more complex picture of how NOEs are linked to well-being or distress. While some studies identified higher levels of anxiety and depression in groups reporting NOEs (Maraldi, 2014), others suggest NOEs are related to happiness (Newberg & Waldman, 2018). Contributing to these mixed findings is the undifferentiated treatment of NOEs-different experiences are often clustered under the same label, or individual experiences are treated in isolation from others.…”
Section: Noes and Mental Healthmentioning
confidence: 99%
“…His participants reported the following kinds of outcomes: wellbeing or positive affective states, ongoing or permanent new state of being, increased present-ness or ability to live in the present, reduced cognitive activity or less identification with thoughts, reduced or disappearance of fear of death, decreased sense of group identity or need for belonging, episodes of intense turmoil or trauma preceding transformation, increased altruism, and enhanced relationships. Also within this special topic section, Newberg and Waldman (2018) draw on the results from 'The Spiritual Awakening Survey', where approximately 2,000 individuals responded to an online survey of people's most intense spiritual experiences (Yaden et al, 2015(Yaden et al, , 2016(Yaden et al, , 2017. In summary, they conclude that in their research of spiritual awakening experiences 'there is a sense of oneness in which the individual awakens to a new relationship with God or the universe and no longer experiences the personal ego but a higher state in which all things are one' (p. 127).…”
Section: Spiritual Awakening: Theory and Measurementmentioning
confidence: 99%